2018
DOI: 10.18608/jla.2018.53.8
|View full text |Cite
|
Sign up to set email alerts
|

Using Temporal Analytics to Detect Inconsistencies Between Learning Design and Students’ Behaviours

Abstract: Extensive research in learning science has established the importance of time management in online learning. Recently, learning analytics (LA) has shed further lights on the temporal characteristics of learning by allowing researchers to capture authentic digital footprints of student learning behaviours. Nonetheless, students' timing of engagement and its relation to learning design (LD) and academic performance have received limited attention. This study investigates to what extent students' timing of engage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 45 publications
0
28
1
Order By: Relevance
“…( 2016 ) proposed that a positive student experience of self-efficacy, tests, motivation, self-regulation and positive interaction with many online events, particularly those that offer feedback, reflection and reasoning, would correlate with academic achievement. In another study to investigate students' engagement in an online course, Nguyen et al . ( 2018 ) found, that high-performing students were studying in advance, while low-performing students showed more catching-up activities.…”
Section: Engagementmentioning
confidence: 99%
See 4 more Smart Citations
“…( 2016 ) proposed that a positive student experience of self-efficacy, tests, motivation, self-regulation and positive interaction with many online events, particularly those that offer feedback, reflection and reasoning, would correlate with academic achievement. In another study to investigate students' engagement in an online course, Nguyen et al . ( 2018 ) found, that high-performing students were studying in advance, while low-performing students showed more catching-up activities.…”
Section: Engagementmentioning
confidence: 99%
“…( 2018 ) found, that high-performing students were studying in advance, while low-performing students showed more catching-up activities. For example, Nguyen et al . ( 2018 ) showed that for certain lessons in the later parts of the course all the students spent significantly more time on learning.…”
Section: Engagementmentioning
confidence: 99%
See 3 more Smart Citations